A Case of Primary Signet-Ring Cell Cervical Carcinoma Treated with Chemoradiation, Brachytherapy, and Adjuvant Hysterectomy - Nicole Salmen; Dominic LaBella; Kenneth Strumpf; Wiley Douglas Bunn; Paul Aridgides (Case Reports in Obstetrics and Gynecology)
Primary signet-ring cell carcinoma of the uterine cervix is a rare subtype of cervical mucinous adenocarcinoma. Approximately 20 cases of primary signet-ring cell carcinoma of the cervix have been reported. Pathologic examination shows that adenocarcinomas with mucin accumulation in intracytoplasmic vacuoles displacing the nucleus indicate signet-ring cell carcinoma. A thorough metastatic workup is needed both for staging and to rule out gastrointestinal tract origin. Due to the rarity of the disease, both the true incidence and optimal management are unknown. Herein, the authors present a case of stage 1B3 primary signet-ring cell cervical carcinoma treated with combined chemotherapy and radiation (including external beam radiation and brachytherapy), followed by resection for residual disease. This case is consistent with limited reports where all surviving patients received surgery as well as 1 surviving patient with bulky disease required with chemoradiation and adjuvant hysterectomy.